PERUBAHAN KEBIJAKAN PEMERINTAH RUSIA TERKAIT LEGALISASI ADOPSI INTERNASIONAL ANAK YATIM PIATU TAHUN 2013 - Indah Sari, Ni Gusti Ayu; Putri, Penny Kurnia; Widya Nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This study aims to analyze the reasons why the Russian Government terminated the adoption agreement with the United States in 2013, using qualitative research methods. Russia has had an adoption partnership with the United States since the 90s. Over time, Russia will have to strengthen its regulatory adoption through bilateral agreements with the United States according to international provisions. But the agreement was suddenly annulled unilaterally by the Russian government after a year. To analyze the issue, this study uses the framework of human security and nation branding, which then finds the answer that the policy changes carried out by the Russian Government are caused by the interests of the state's image of its identity and culture, and emphasizes the state's attention to providing protection to its people by ensuring aspects human security as part of international norms. Keywords: National Image, Human Security, Policy Change, Russia